Method for rapidly representing filling area of embedded boron nitride nanotube and application
By using SEM imaging under specific conditions and combining it with image processing, the problem of difficult accurate measurement of the embedded boron nitride nanotube filling area in the existing technology was solved, and fast, low-cost high-resolution imaging and measurement were achieved.
Patent Information
- Application Number
- CN202511020217.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-23
- Publication Date
- 2025-09-30
AI Technical Summary
Existing technologies make it difficult to quickly and accurately obtain information such as the length, diameter, and position of the embedded boron nitride nanotube filling area, and the cost is high and the operation is complicated.
Scanning electron microscopy (SEM) was used for imaging under specific conditions, and the filling area of the embedding was identified by using grayscale differences. By adjusting parameters such as acceleration voltage, working distance, and magnification, clear images of the filling area were obtained, and the length and diameter were measured using image processing software.
The method achieves fast, low-cost, and simple operation to characterize the embedded boron nitride nanotube filling area, obtains high-resolution length, diameter, and position information, and is minimally destructive to the sample.
Smart Images

Figure CN120721772A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of analysis and testing technology, and in particular to a method for rapidly characterizing a region filled with embedded boron nitride nanotubes and its application. Background Art
[0002] Boron nitride nanotubes have attracted widespread attention in many fields due to their advantages such as wide band gap, excellent mechanical strength, and high thermal conductivity. In addition, studies have shown that embedded boron nitride nanotubes obtained by encapsulating guest molecules in the lumen of boron nitride nanotubes exhibit richer and more unique physical properties. Usually, in order to ensure the successful synthesis of embedded boron nitride nanotubes and obtain information such as the length, diameter, and position of the filling area, characterization techniques such as transmission electron microscopy (TEM), Raman spectroscopy (Raman), and X-ray photoelectron spectroscopy (XPS) are commonly used in the field for characterization and measurement. However, these characterization techniques often have problems such as complex operation, high cost, low resolution and accuracy, making it difficult to quickly and accurately obtain images of the embedded boron nitride nanotube filling area.
[0003] Specifically, Chinese invention patent CN 10789300 A and literature (Phys. Status SolidiRRL 2023, 17, 2200284) both propose using transmission electron microscopy (TEM) characterization methods to confirm whether the guest substance is successfully filled into the inner cavity of the boron nitride nanotube. However, TEM has the disadvantages of complex sample preparation, cumbersome operation process, long time period and high price cost; secondly, common spectroscopic characterization methods such as Raman spectroscopy and infrared spectroscopy (FTIR) can be used to characterize whether there is filling. Although these methods have the advantages of simple operation, convenient sample preparation, short time period and low cost, they also have the disadvantages of not being able to accurately obtain imaging of the filling area of the embedded boron nitride nanotubes, and not being able to obtain more specific information such as the length, diameter and position of the filling area.
[0004] Scanning electron microscopy (SEM) is a common characterization technique with advantages such as rapid imaging, large-area imaging, and high resolution. It can also provide information on both the surface morphology and composition of materials, making it widely used in the characterization of nanomaterials. However, while SEM is often used to observe various embedded tubular nanomaterials, there are currently no reports on using SEM to observe the filling area of embedded boron nitride nanotubes and measure the location, length, and diameter of the filling area. The potential of SEM for observing the filling area of embedded boron nitride nanotubes has not yet been recognized in the field. Summary of the Invention
[0005] In view of the shortcomings of the prior art, the present invention aims to provide a method and application for rapidly characterizing the filling area of embedded boron nitride nanotubes.
[0006] To achieve the aforementioned object of the invention, the technical solutions adopted by the present invention include:
[0007] In a first aspect, the present invention provides a method for rapidly characterizing an area filled with embedded boron nitride nanotubes, comprising:
[0008] preparing an observation sample, wherein the observation sample comprises a single dispersed embedded boron nitride nanotube, wherein the embedded boron nitride nanotube comprises a boron nitride nanotube and an embedded object in the tube cavity;
[0009] The observation sample is imaged using a scanning electron microscope at an accelerating voltage of 5-7 kV to obtain an observation image. In the observation image, the grayscale of the filled region of the embedment is different from the grayscale of the unfilled lumen region.
[0010] In a second aspect, the present invention further provides an application of the above method in preparing embedded boron nitride nanotubes.
[0011] Based on the above technical solution, compared with the prior art, the beneficial effects of the present invention include:
[0012] The present invention uses a scanning electron microscope and sets specific condition parameters to confirm the filler embedded in the boron nitride nanotubes, obtaining a clear image of the filler object within the tube cavity and intuitively displaying information such as the length, diameter and position of the filler object. This testing method is short in time, low in price, simple to operate, and less destructive to the sample.
[0013] The above description is only an overview of the technical solution of the present invention. In order to enable those skilled in the art to more clearly understand the technical means of this application and implement them according to the contents of the specification, the following is an explanation of the preferred embodiments of the present invention with detailed drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 This is an SEM image of embedded boron nitride nanotubes provided in a typical embodiment of the present invention;
[0015] Figure 2 This is a schematic diagram of the operation process of grayscale segmentation and recognition of an SEM image of embedded boron nitride nanotubes, provided by a typical embodiment of the present invention;
[0016] Figure 3 This is a statistical distribution diagram of the length of the filling area of embedded boron nitride nanotubes provided in a typical embodiment of the present invention;
[0017] Figure 4is an SEM image of embedded boron nitride nanotubes provided by another typical embodiment of the present invention;
[0018] Figure 5 This is an SEM image of embedded boron nitride nanotubes provided in another typical embodiment of the present invention;
[0019] Figure 6 This is an SEM image of embedded boron nitride nanotubes provided in a typical comparative example of the present invention;
[0020] Figure 7 is another typical comparison and an SEM image of embedded boron nitride nanotubes provided by an embodiment of the present invention;
[0021] Figure 8 This is an SEM image of embedded boron nitride nanotubes provided by another typical comparative example of the present invention. DETAILED DESCRIPTION
[0022] Chinese invention patent CN 10789300 A related to the technical solution of the present invention discloses a method for preparing boron nitride nanotubes filled with nano-iron particles by self-propagating reaction, and uses transmission electron microscopy (TEM) to confirm the filling of the boron nitride nanotubes (filled with nano-iron particles with a diameter of 80nm), uses scanning electron microscopy (SEM) to characterize the large-area interlaced boron nitride nanotube network, and uses scanning electron microscopy (SEM) to observe the surface morphology, length (5-120μm) and diameter (50-250nm) of the embedded boron nitride nanotubes. X-ray diffraction analysis (XRD) confirms the hexagonal boron nitride structure and the presence of iron phase, infrared spectroscopy (FTIR) detects the characteristic peak of BN bonds, and energy dispersive X-ray spectroscopy (EDS) analyzes the element ratio (B:N:Fe≈I:1:0.2), which comprehensively proves that the iron particles are successfully filled in the boron nitride nanotubes. Among them, only TEM characterization can obtain the imaging of the filling guest in the lumen of embedded boron nitride nanotubes, thereby confirming the filling and obtaining the size and position of the filled area.
[0023] The literature Phys.Status SolidiRRL 2023, 17, 2200284 reported that the graphene nanoribbon precursor 1,2,4-trichlorobenzene was encapsulated into carbon boron nitride nanotubes at room temperature and annealed, successfully preparing graphene nanoribbons. The graphene nanoribbons formed inside were observed by high-resolution transmission electron microscopy (HRTEM), and the graphene characteristic G peak (1598cm- 1 ) and scanning transmission electron microscopy combined with energy dispersive spectroscopy (STEM-EDS) element mapping confirmed the presence of carbon elements inside the boron nitride nanotubes, proving the success of the filling.
[0024] The above technical solution is obviously more complicated and requires identification of specific element energy spectra to confirm the filling, and cannot be widely applied to many different fillers.
[0025] In view of the shortcomings of the prior art, the inventors of this case, after long-term research and extensive practice, have proposed the technical solution of the present invention. The following will further explain this technical solution, its implementation process and principles.
[0026] In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention may also be implemented in other ways different from those described herein. Therefore, the scope of protection of the present invention is not limited to the specific embodiments disclosed below.
[0027] The embodiment of the present invention provides a method for rapidly characterizing an area filled with embedded boron nitride nanotubes, which comprises the following steps:
[0028] preparing an observation sample, wherein the observation sample comprises a single dispersed embedded boron nitride nanotube, wherein the embedded boron nitride nanotube comprises a boron nitride nanotube and an embedded object in the tube cavity;
[0029] The observation sample is imaged using a scanning electron microscope at an accelerating voltage of 5-7 kV to obtain an observation image. In the observation image, the grayscale of the filled region of the embedment is different from the grayscale of the unfilled lumen region.
[0030] In some embodiments, the preparation process of the observation sample may specifically include:
[0031] The embedded boron nitride nanotubes are attached to the surface of the substrate in a dispersed state;
[0032] The substrate with the embedded boron nitride nanotubes attached thereto is fixed on a sample stage of a scanning electron microscope through conductive glue.
[0033] In some embodiments, the preparation process of the observation sample may specifically include:
[0034] preparing a dispersion of the embedded boron nitride nanotubes;
[0035] The dispersion is spin-coated on the surface of the substrate and dried to obtain a substrate with the embedded boron nitride nanotubes attached thereto.
[0036] In some embodiments, the concentration of the embedded boron nitride nanotubes in the dispersion is 80-120 mg / L.
[0037] In some embodiments, the dispersion is sonicated for 5-10 min.
[0038] In some embodiments, the dispersion is spin-coated at a speed of 2000-4000 r / min, an acceleration of 800-1200, and a time of 40-80 s.
[0039] In some embodiments, the substrate includes any one of a SiO2 / Si mixed substrate and a Si conductive substrate.
[0040] In some embodiments, the observation distance for imaging using the scanning electron microscope is 8-9.5 mm.
[0041] In some embodiments, the imaging performed using the scanning electron microscope has a magnification of 80-120K.
[0042] In some embodiments, the electron beam incident angle for imaging using the scanning electron microscope is 90°.
[0043] In some embodiments, the capture time for imaging using the scanning electron microscope is 180 ms.
[0044] In some embodiments, the method may further comprise the steps of:
[0045] Based on the difference in grayscale, the length, diameter and position of the filling area are identified.
[0046] In some embodiments, the above process may specifically include:
[0047] performing grayscale statistics along the axial direction of the embedded boron nitride nanotubes to obtain axial grayscale distribution;
[0048] A grayscale threshold value that can represent the filling area based on the axial grayscale distribution statistics;
[0049] An image region with a grayscale above the grayscale threshold is used as the filling region, and statistics are collected on the length, diameter, and position of the filling region.
[0050] In some embodiments, the length and diameter are measured at multiple points in the filling area, and the statistical average value is used as the representative length and representative diameter of the filling area.
[0051] Based on the above technical solution, a specific embodiment of the present invention provides a rapid characterization method for regions filled with embedded boron nitride nanotubes. For example, an ethanol dispersion of embedded boron nitride nanotubes can be evenly spin-coated onto a 300nm thick SiO2 / Si hybrid substrate. Using simple scanning electron microscopy (SEM) technology, at an appropriate accelerating voltage, working distance, and magnification, high-resolution imaging of the embedded boron nitride-filled region, as well as length, diameter, and position information, can be rapidly obtained. This characterization process is simple, low-cost, and rapid.
[0052] The embodiment of the present invention further provides the use of the method provided by any of the above embodiments in preparing embedded boron nitride nanotubes.
[0053] The technical solution of the present invention is further described in detail below through several embodiments and in conjunction with the accompanying drawings. However, the selected embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention.
[0054] Example 1
[0055] 1. Disperse the boron nitride nanotubes embedded with molybdenum disulfide in ethanol at a concentration of 100 mg / L and disperse them into a single boron nitride nanotube dispersion by ultrasonication for about 5-10 minutes.
[0056] 2. Place a 300nm thick SiO2 / Si hybrid substrate (i.e., the thickness of the SiO2 layer on the surface of the Si substrate is 300nm) on a spin coating platform, and use a pipette to drop the solution on the substrate to ensure that the solution completely covers the substrate.
[0057] 3. Spin coating and drying were performed at a rotation speed of 3000 rpm, an acceleration of 1000 (i.e., accelerating from rest to 3000 rpm in 3 seconds), and a spin coating time of 60 seconds to obtain a single embedded boron nitride nanotube sample dispersed on the substrate.
[0058] 4. The sample was attached to the microscope stage using conductive silver glue and placed into the vacuum chamber of a scanning electron microscope. Under an accelerating voltage of 5 kV, a working distance of 8.7 mm, and a magnification of 100 K, appropriate brightness and contrast were adjusted for observation, resulting in a clear image of the filling area embedded with boron nitride nanotubes.
[0059] 5. Collect clear SEM images and use Image J software to measure the length and diameter of the embedded boron nitride nanotube filler, and make a statistical distribution graph of the length and diameter. During the measurement, take 3-5 points for each section of the filler and measure the average value.
[0060] Figure 1 This is a SEM image of the embedded boron nitride nanotubes obtained in the test of this embodiment. The length, diameter and position of the filler can be clearly seen from the image.
[0061] Figure 2 In Example 1 of the present invention, the gray value distribution of the embedded boron nitride nanotube filling area was measured using Image J. The length information of the filling can be clearly seen from the figure, for example, Figure 2 The starting value of the rising segment of the grayscale curve shown is used as the grayscale threshold, and the segments above the grayscale threshold are considered to belong to the filling area.
[0062] Figure 3 In Example 1 of the present invention, the lengths of a large number of fillers embedded in boron nitride nanotubes were collected and counted using Image J, and a statistical distribution diagram of the filler lengths was drawn. It can be seen from the diagram that the lengths of the fillers are mainly concentrated below 400 nm.
[0063] Example 2
[0064] This embodiment is substantially the same as the first embodiment, with the main differences being the embedded material and SEM observation conditions. Specifically, the embedded material is replaced with silver iodide (AgI), the accelerating voltage is 7 kV, the working distance is 8 mm, and the magnification is 80K.
[0065] The SEM images observed in this embodiment are as follows Figure 4 shown.
[0066] Example 3
[0067] This embodiment is substantially the same as embodiment 1, with the main difference being the different SEM observation conditions. Specifically, the material of the embedding is replaced with molybdenum trioxide (MoO 3 ), the acceleration voltage is 6 kV, the working distance is 9.5 mm, and the magnification is 120K.
[0068] The SEM images observed in this embodiment are as follows Figure 5 shown.
[0069] Example 4
[0070] This embodiment is substantially the same as embodiment 1, with the main differences being:
[0071] The substrate was replaced with a Si conductive substrate.
[0072] In the above Examples 2-4, the morphology of the embedded objects in the boron nitride nanotubes can be clearly observed, and their length, diameter and position can be determined.
[0073] Comparative Example 1
[0074] This comparative example is substantially the same as Example 1, except that:
[0075] The accelerating voltage was adjusted to 3 kV for observation.
[0076] When the acceleration voltage is less than the appropriate voltage window, it can be clearly observed that the grayscale difference between the embedded object and the unfilled area in the boron nitride nanotube disappears, and the filled area and the unfilled area cannot be distinguished at this time.
[0077] The SEM images observed in this comparative example are as follows Figure 6 shown.
[0078] In multiple voltage tests, it was found that if the voltage was inappropriate (less than 5kV), the image of the embedded object would not be clearly displayed. If it was greater than 7kV, the embedded boron nitride tube would deform in the image, resulting in image distortion of the embedded object and possible damage to the sample.
[0079] Comparative Example 2
[0080] This comparative example is substantially the same as Example 1, except that:
[0081] Adjust the electron beam incident angle to 60°
[0082] When the electron beam incident angle is changed from 90° perpendicular, the contrast between the image of the embedment and the boron nitride tube decreases, and the boundary between the filled and unfilled areas becomes unclear. This leads to inaccurate determination of the embedment's length, diameter, and precise position. However, a certain degree of imaging can still be achieved, indicating that a 90° electron beam incident angle is an optimal parameter for accurately observing the embedment of boron nitride nanotubes qualitatively and quantitatively.
[0083] The SEM images observed in this comparative example are as follows Figure 7 shown.
[0084] Comparative Example 3
[0085] This comparative example is substantially the same as Example 1, except that:
[0086] Replace the substrate with a quartz substrate.
[0087] Using the same parameters, we found that a large amount of charge accumulated on the quartz substrate, making the image too bright and difficult to find the sample. Furthermore, no matter what voltage was used, it was impossible to obtain a clear image of the embedded boron nitride tube. This indicates that an unsuitable substrate, such as a quartz substrate, will produce a large amount of accumulated charge, making the image too bright and the embedded object difficult to clearly image.
[0088] The SEM images observed in this comparative example are as follows Figure 8 shown.
[0089] Comparative Example 4
[0090] This comparative example is substantially the same as Example 1, except that:
[0091] The embedded boron nitride nanotubes are replaced with embedded carbon nanotubes.
[0092] Using the same substrate, the same sample preparation method and the same SEM conditions for observation, when the resolution of the electron microscope equipment is relatively fine, only the morphology of the embedding can be roughly seen. The contrast between the embedding pattern and the nanotube image is small, and the boundary is relatively blurred. It can qualitatively determine the presence of embeddings in carbon nanotubes, but cannot accurately characterize their precise position and size.
[0093] Based on the above embodiments and comparative examples, it can be clearly seen that the embodiments of the present invention utilize a scanning electron microscope and set specific condition parameters to confirm the filler embedded in the boron nitride nanotubes, obtain clear imaging of the filling object in the tube cavity, and can intuitively display information such as the length, diameter, and position of the filling object. This testing method is short in time, low in price, simple to operate, and less destructive to the sample.
[0094] It should be understood that the above embodiments are merely illustrative of the technical concepts and features of the present invention. Their purpose is to enable those skilled in the art to understand the contents of the present invention and implement them accordingly. They are not intended to limit the scope of protection of the present invention. Any equivalent variations or modifications made in accordance with the spirit and substance of the present invention are intended to be encompassed within the scope of protection of the present invention.
Claims
1. A method for rapidly characterizing the filling area of embedded boron nitride nanotubes, characterized in that: include: preparing an observation sample, wherein the observation sample comprises a single dispersed embedded boron nitride nanotube, wherein the embedded boron nitride nanotube comprises a boron nitride nanotube and an embedded object in the tube cavity; The observation sample is imaged using a scanning electron microscope at an accelerating voltage of 5-7 kV to obtain an observation image. In the observation image, the grayscale of the filled region of the embedment is different from the grayscale of the unfilled lumen region.
2. The method according to claim 1, characterized in that The preparation process of the observation sample includes: The embedded boron nitride nanotubes are attached to the surface of the substrate in a dispersed state; The substrate with the embedded boron nitride nanotubes attached thereto is fixed on a sample stage of a scanning electron microscope through conductive glue.
3. The method according to claim 2, characterized in that The preparation process of the observation sample specifically includes: preparing a dispersion of the embedded boron nitride nanotubes; The dispersion is spin-coated on the surface of the substrate and dried to obtain a substrate with the embedded boron nitride nanotubes attached thereto.
4. The method according to claim 3, characterized in that The concentration of embedded boron nitride nanotubes in the dispersion is 80-120 mg / L; and / or, the dispersion is subjected to ultrasonic treatment for 5-10 min; And / or, the spin coating speed of the dispersion is 2000-4000 r / min, the spin coating acceleration is 800-1200, and the spin coating time is 40-80 s.
5. The method according to any one of claims 2 to 4, characterized in that The substrate includes any one of a SiO2 / Si mixed substrate and a Si conductive substrate.
6. The method according to claim 1, characterized in that The observation distance for imaging using the scanning electron microscope is 8-9.5 mm, and / or the magnification is 80-120K; the electron beam incident angle is 90°; and the capture time is 180 ms.
7. The method according to claim 1, characterized in that Also includes: Based on the difference in grayscale, the length, diameter and position of the filling area are identified.
8. The method according to claim 7, characterized in that Specifically include: performing grayscale statistics along the axial direction of the embedded boron nitride nanotubes to obtain axial grayscale distribution; A grayscale threshold value that can represent the filling area based on the axial grayscale distribution statistics; An image region with a grayscale above the grayscale threshold is used as the filling region, and statistics are collected on the length, diameter, and position of the filling region.
9. The method according to claim 8, characterized in that In the filling area, multiple points are taken to measure the length and diameter, and the statistical average value is used as the representative length and representative diameter of the filling area.
10. Use of the method according to any one of claims 1 to 9 in preparing embedded boron nitride nanotubes.
Citation Information
Cited By
Amplification power calibration method of scanning electron microscope
CN121114114A